A numerical investigation of the drag forces on a fleet of underwater gliders - Prakasan, A. (American Scientific Publishers, 2017)
Land vehicle platooning improves the overall fuel economy of the fleet by decreasing its total air resistance. In this work, we investigate the drag forces on a five-glider fleet of underwater gliders, both in a conventional “V” and an alternative, more compact, 3D “V” formation. In addition, the effect of transverse, longitudinal and vertical separation of these gliders on the drag forces is studied. Our study uses ANSYS Fluent with Re- Normalization Group (RNG) k-epsilon model with non-equilibrium wall function as the turbulence model. Based on the simulation results, a low drag of 2.7 N, similar that achieved in a “V” formation, can be achieved with the more compact 3D “V” formation, which has a smaller footprint. The lowest drag was achieved at 1.1 m longitudinal and transverse separation with 0.2 m vertical separation for a 1.03 m glider with a 0.28 m diameter and 0.98 m wingspan. © 2017 American Scientific Publishers All rights reserved.